THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN LINGUISTICS: OPPORTUNITIES AND CHALLENGES: THE ROLE OF ARTIFICIAL INTELLIGENCE IN MODERN LINGUISTICS: OPPORTUNITIES AND CHALLENGES - Utebaeva, Aziza (Журнал иностранных языков и лингвистики, 2025)
In recent years, artificial intelligence (AI) technologies have caused profound changes in almost all areas of science. In particular, the use of artificial intelligence tools in the field of linguistics has become the basis for a new stage in the development of science. Language models, automatic translation systems, speech recognition, and natural language processing (NLP) tools are widely used in linguistic practice. This article analyzes the capabilities, relevance, impact on linguistic research, and potential threats of these technologies.